Black cross or the files of the plot against Lebanon - Strasser, Theo; Anajah Press (Melbourne ?: Anajah Press ?, 2015)
An artist's book of images and text by Theo Strasser, compiled from photographs (both his own and found images), as well as photocopied and handworked collages. Bound with black thread in a stitched booklet with original monochrome handpainted covers.
Cover title.
Limited edition of 50 numbered copies signed by the artist.
National Library's SR copy is no. 5/50.
Keywords: Artists' books -- Victoria; Zines -- Victoria; Black -- Pictorial works; Crosses -- Pictorial works; Australian